2017
DOI: 10.1021/acs.organomet.7b00635
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous-Phase Chemistry of η3-Allylpalladium(II) Complexes with SulfonatedN-Heterocyclic Carbene Ligands: Solvent Effects in the Protolysis of Pd–C Bonds and Suzuki–Miyaura Reactions

Abstract: The synthesis of water-soluble η 3 -allyl Pd(II) complexes containing sulfonated N-heterocyclic carbene (NHC) ligands of general formula [Pd(NHC) n (η 3 -allyl)Cl 2−n ] is reported (n = 1 (1) or 2 ( 8)). Monocarbene complexes were obtained with the most sterically hindered NHC ligands, and biscarbenes with the less sterically hindered NHCs. The behavior of the isolated complexes in water under acidic, neutral, or alkaline conditions has been studied. The complexes are rather stable in water under neutral or al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…as anticancer agents. 26,27 They can be readily prepared from the commercially available dimeric allyl–palladium complex and the respective imidazolium salt precursor. Herein, we chose a N -isopropylated CHIM derivative instead of the N -methylated salt as an imidazolium precursor for the synthesis of CHIM–Pd since more bulky N -substituents have been described to be beneficial for complex stability in aqueous medium and to lead preferentially to monocarbene complex formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…as anticancer agents. 26,27 They can be readily prepared from the commercially available dimeric allyl–palladium complex and the respective imidazolium salt precursor. Herein, we chose a N -isopropylated CHIM derivative instead of the N -methylated salt as an imidazolium precursor for the synthesis of CHIM–Pd since more bulky N -substituents have been described to be beneficial for complex stability in aqueous medium and to lead preferentially to monocarbene complex formation.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we chose a N -isopropylated CHIM derivative instead of the N -methylated salt as an imidazolium precursor for the synthesis of CHIM–Pd since more bulky N -substituents have been described to be beneficial for complex stability in aqueous medium and to lead preferentially to monocarbene complex formation. 27 At the same time, isopropyl substituents were expected to still be small enough to only marginally affect faithful membrane integration. 28 The integration of CHIM–Pd was quantified by single-cell inductively coupled plasma mass spectrometry (scICP-MS).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, de Jesús and co-workers prepared and studied a series of water-soluble η 3 -allylpalladium(II) complexes with sulfonated N-heterocyclic carbene ligands. 92 In particular, complex 225 is an active precatalyst for the Suzuki-Miyaura coupling of water-soluble aryl chlorides in neat water under moderate conditions (typically, 0.5 mol% Pd, 60 °C) (Figure 3). Remarkably, under such conditions, the activation of the precatalyst is likely to occur by transmetalation with the arylboronic acid followed by reductive elimination of (Ar)allyl.…”
Section: Scheme 65 Suzuki-miyaura Coupling Catalyzed By Unsymmetricalmentioning
confidence: 99%
“…In the studies by de Jesús and coworkers, Pd/NHC complexes containing -SO 3 Na groups showed high solubility in water and activity in the Suzuki-Miyaura reaction carried out in the aqueous phase. 30,31 Plenio and coworkers reported an easy method for the preparation of -SO 3 Na substituted Pd/ NHC complexes, which showed high yields in Sonogashira and Suzuki-Miyaura cross-couplings. 32 Tuning biological activity is the key application of functional group effects in the medicinal and pharmaceutical applications of Pd/NHC complexes.…”
Section: Introductionmentioning
confidence: 99%